Policy and Practice in Rural Tanzania: Grazing, Fishing and Farming at the Local–Global Interface - Antonio Allegretti (The White Horse Press, 2022)
Who are the rural people of Africa? What does it mean to be part of a 'rural' community in contemporary Tanzania? And why is it important to debate questions of African rurality beyond the mere GDP contribution of rural land-based production? This book seeks to address questions like these. Rural people(s) in contemporary Africa are often conceived of in terms of how to efficiently integrate them into international markets and global value chains; this book analyses the question of integration of rural people in Tanzania by delving into how they deal with local-global connections and engage with policy objectives on their own terms, between local forms of associational life and global markets. In so doing, it explores local socio-economic dynamics that find little space in the national and global policy vision of a rural sector geared towards growth – a vision that is peculiar to African states, including Tanzania. Informed by anthropological theory and de-re-agrarianisation/de-re-peasantisation debates, and grounded in ethnographic evidence, the book eschews 'orthodox' approaches that see (rural) people as passive recipients of policies, and policies as instruments of oppression. Instead, it departs from the rural land/place-based practices of grazing, fishing and farming to look at rurality in Tanzania as a blend of old and new meanings, values and practices at the local-global interface, continually reshuffled as rural people encounter different social and economic spheres. As the world rediscovers the urgency of questions connected to neo-colonialism and de-colonisation, this book brings to the forefront the position, worldview and ambitions of African rural peoples intersecting with international policy models, visions and objectives.
Keywords: 330; Business & Economics; Development; Social Science; Anthropology; Social Science; Developing & Emerging Countries